Combining Donor Characteristics with Immunohistological Data Improves the Prediction of Islet Isolation Success. (10th October 2016) - Berkova, Zuzana; Saudek, Frantisek; Girman, Peter; Zacharovova, Klara; Kriz, Jan; Fabryova, Eva; Leontovyc, Ivan; Koblas, Tomas; Kosinova, Lucie; Neskudla, Tomas; Vavrova, Ema; Habart, David; et al.
Abstract : Variability of pancreatic donors may significantly impact the success of islet isolation. The aim of this study was to evaluate donor factors associated with isolation failure and to investigate whether immunohistology could contribute to organ selection. Donor characteristics were evaluated for both successful (n = 61 ) and failed (n = 98 ) islet isolations. Samples of donor pancreatic tissue (n = 78 ) were taken for immunohistochemical examination. Islet isolations with 250000 islet equivalents were considered successful. We confirmed that BMI of less than 25 kg/m 2 (P < 0.001 ), cold ischemia time more than 8 hours (P < 0.01 ), hospitalization longer than 96 hours (P < 0.05 ), higher catecholamine doses (P < 0.05 ), and edematous pancreases (P < 0.01 ) all unfavorably affected isolation outcome. Subsequent immunohistochemical examination of donor pancreases confirmed significant differences in insulin-positive areas (P < 0.001 ). ROC analyses then established that the insulin-positive area in the pancreas could be used to predict the likely success of islet isolation (P < 0.001 ). At the optimal cutoff point (>1.02%), sensitivity and specificity were 89% and 76%, respectively. To conclude, while the insulin-positive area, determined preislet isolation, as a single variable, is sufficient to predict isolation outcome and helps to improve the success of this procedure, its combination with the established donor scoring system might further improve organ selection.